2007
DOI: 10.1111/j.1365-2796.2007.01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Travel and venous thrombosis: a systematic review

Abstract: In the past decade, numerous publications on the association between venous thrombosis (VT) and travel have been published. Relative and absolute risks of VT after travel, and particularly after travel by air, have been studied in case-control and observational follow-up studies, whereas the effect of prophylaxis has been studied through intervention trials of asymptomatic clots. The mechanism responsible for the association between travel and VT was addressed in pathophysiologic studies. Here, we systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 69 publications
(126 reference statements)
2
84
0
Order By: Relevance
“…A dose-response relationship was identifi ed, with an 18% higher risk of VTE for each 2-h increase in travel duration. 122,123 However, the overall absolute incidence of a symptomatic VTE in the month following a fl ight . 4 h is 1 in 4,600 fl ights, 124 with a reported incidence of asymptomatic VTE on arrival from a trip ranging from 0% to 1.5%.…”
Section: Risk Of Vtementioning
confidence: 99%
See 2 more Smart Citations
“…A dose-response relationship was identifi ed, with an 18% higher risk of VTE for each 2-h increase in travel duration. 122,123 However, the overall absolute incidence of a symptomatic VTE in the month following a fl ight . 4 h is 1 in 4,600 fl ights, 124 with a reported incidence of asymptomatic VTE on arrival from a trip ranging from 0% to 1.5%.…”
Section: Risk Of Vtementioning
confidence: 99%
“…4 h is 1 in 4,600 fl ights, 124 with a reported incidence of asymptomatic VTE on arrival from a trip ranging from 0% to 1.5%. 123 The incidence varies by the type and duration of travel and by individual risk factors. [125][126][127] Thrombosis risk also appears to be increased for travel by car, bus, or train.…”
Section: Risk Of Vtementioning
confidence: 99%
See 1 more Smart Citation
“…Severe cases of PE immediately after a flight are rare, especially in flights taking less than eight hours (45) . In flights lasting more than twelvehours, therate is estimated at five per million (46) . Notable in this study is the fact that; not all cases of PE occur as a result of travel.…”
Section: Resultsmentioning
confidence: 99%
“…Notable in this study is the fact that; not all cases of PE occur as a result of travel. If the condition has to be associated with travel, it must have occurred up to eight weeks after the travel (46) . In eleven case controlled studies, it has been reported that the risk of VTE cases related to travel is more evident in individuals with preexisting risk factors (6,19,24,26,34,44,51,57,58,64,82) .…”
Section: Resultsmentioning
confidence: 99%